Optical coherence tomography and fundus autofluorescence imaging study of chorioretinal atrophy involving the macula in Alagille syndrome - Makino S (Dove Medical Press, 2012)
Shinji Makino, Yuko Ohkubo, Hironobu TampoDepartment of Ophthalmology, Jichi Medical University, Shimotsuke, Tochigi, JapanAbstract: We report the first case in the literature of chorioretinal atrophy involving the macula in an 11-year-old girl with Alagille syndrome, as examined by optical coherence tomography, and fundus autofluorescence imaging. Funduscopy revealed diffuse choroidal hypopigmentation with increased visibility of the choroidal vessels and symmetric, well circumscribed macular discoloration. Anomalous oblique configuration of the optic disc and peripapillary tortuous vessels were also detected. Optical coherence tomography demonstrated decreased retinal thickness, especially the outer retinal layer, and the photoreceptor inner segment/outer segment junctions were irregular and discontinued, corresponding to macular discoloration. Fundus autofluorescence imaging clearly defined hypofluorescent areas in the peripapillary regions that extended along the macula and had a sleep mask appearance. We suggest that transient hypovitaminosis due to Alagille syndrome early in life might contribute to the retinal degeneration seen in this case.Keywords: Alagille syndrome, chorioretinal atrophy, optical coherence tomography, fundus autofluorescence imaging, hypovitaminosis